What mothers wish for their children: Mother-constructed higher education future orientation and its antecedents - Rachel Seginer; Adi Yoavi (Revista de Psicología)
This study examines the future orientation regarding higher education mothers wish for their children and four of its antecedents. The antecedents are: mothers’ educational attainment, mothers’ educational expectations, and mothers’ supported children’s motivation applying to two types: autonomous and controlled. Review of earlier research led to the construction of a multiple-step model indicating that mothers’ educational attainment impacts mothers’ educational expectations which in turn impacts the education-related future orientation mothers wish their children to develop indirectly, via mothers’ wish to differentially transmit to their children motivational autonomy and control. Employing Structural Equation Model (Amos 26), the mothers’ constructed model was examined with data collected from 179 mothers of Israeli Jewish children and youths, which resulted in a good fit of the multiple step model to the data. Specifically, analysis supported the impact of mothers’ wish to transmit motivational autonomy --but not of mothers’ wish to transmit motivational control -- on mothers’ wished-for education-related future orientation. Discussion addresses the importance of future thinking for impacting present ideas applying to mother-constructed higher education future orientation for their children academic achievement, and calls for further empirical analysis of its impact on mother’ behavior prompting academic achievement and its impact on children’s academic achievement, and for further testing of the model on diverse samples.